Объяснение: * * * cos(-α) =cosα , sin2α=2sinα*cosα и формулы
приведения * * *
1) ( 1 +sin(4π -(π/2 +α) )+ cos(2π-2α) ) / (2sinα*cosα - sinα) =
( 1 - cosα+ cos2α ) / (2sinα*cosα - sinα) =(2cos²α -cosα) / (2cosα -1)sinα=
(2cosα -1)cosα / (2cosα -1)sinα = ctgα .
2) ( sin²α - 4sin²(α/2) ) / ( sin²α - 4+4sin²(α/2) ) =
( 4sin²(α/2) cos²(α/2) - 4sin²(α/2) ) / ( 4sin²(α/2) cos²(α/2) - 4(1 -sin²(α/2) ) =
- 4sin²(α/2) (1 - cos²(α/2) ) / - 4cos²(α/2)( 1 -sin²(α/2) ) =
sin⁴(α/2) / cos⁴(α/2)= tg⁴(α/2) .
3) (cos²α -sin²α ) / (1+sin2α) =
|| * * * 1+sin2α= cos²α+sin²α+2sinαcosα =(cosα+sinα)² * * * ||
= (cosα -sinα )(cosα+sinα) /(cosα+sinα)²= (cosα -sinα)/(cosα+sinα)
4) ( sin(α+β) - sin(α -β) ) / ( sin(α+β) +sin(α -β) ) =
|| sinα -sinβ =2sin( (α -β)/2 ) *cos( (α +β)/2 ) ||
|| sinα+sinβ =2sin( (α+β)/2 ) *cos( (α -β)/2 ) ||
= 2 sinβcosα / 2 sinαcosβ =(cosα / sinα) *(sinβ/cosβ) = ctgα *tgβ =
ctgα / ctg β.
* * * * * * * по другому * * * * * * *
( sin(α+β) - sin(α -β) ) / ( sin(α+β) +sin(α -β) ) =
( sinαcosβ+cosα*sinβ - (sinαcosβ-cosα*sinβ) ) *
1/ ( sinαcosβ+cosα*sinβ+ sinαcosβ-cosα*sinβ ) =
2cosα*sinβ /2 sinαcosβ =ctgα /ctgβ
* * * * * * * * * * * * * * * * * * * * *
5) ( (1+cosx)/sinx )*(1+ ( (1 -cosx)/sinx )² ) =
( (1+cosx)/sinx )*(sin²x +1 -2cosx+cos²x )/sin²x ) =
( (1+cosx)/sinx )*( 2(1 -cosx))/sin²x ) = 2(1+cosx)(1-cosx) /sin³x =
2(1 - cos²x) /sin³x =2sin²x/ sin³x = 2 / sinx .
* * * * * * * по другому * * * * * * *
= ( 2cos²(x/2) / 2sin(x/2)*cos(x/2) )*(1+ ( 2sin²(x/2) / 2sin(x/2)*cos(x/2) )² ) =
(cos(x/2) / sin(x/2) )*( 1 + sin²(x/2) / cos²(x/2) ) =
(cos(x/2) /sin(x/2) )*( ( cos²(x/2) + sin²(x/2) ) /cos²(x/2) ) =
(cos(x/2) /sin(x/2) )* ( 1 / cos²(x/2) ) = 1 /( cos(x/2)*sin(x/2) ) =2/sinx
* * * * * * * * * * * * * * * * * * * * *
1) 39;
2) -1,44;
3) 187/324;
4) -11/20;
5) 0;
6) -27 3/36;
7) 800
Пошаговое объяснение:
1) 20² - 19² = (20 - 19)(20 + 19) = 1 * 39 = 39;
2) 3,5² - 3,7² = (3,5 - 3,7)(3,5 + 3,7) = (-0,2) * 7,2 = -1,44;
3) (7/9)² - (1/6)² = (7/9 - 1/6)(7/9 + 1/6) = 11/18 * 17/18 = 187/324;
4) (3/10)² - (4/5)² = (3/10 - 4/5)(3/10 + 4/5) = -1/2 * 11/10 = -11/20;
5) (2 1/7)² - (2 1/7)² = (2 1/7 - 2 1/7)(2 1/7 + 2 1/7) = 0 * 4 2/7 = 0;
6) (5 1/6)² - (7 1/3)² = (5 1/6 - 7 1/3)(5 1/6 + 7 1/3) = -13/6 * 75/6 = -27 3/36;
7) 54² - 46² = (54 - 46)(54 + 46) = 8 * 100 = 800
у = |х| + 3х.